A study on the intention to formally dispose E-Waste among residents in Taman Bahau, Negeri Sembilan - Muhammad Izzul Afiq Zulkifli; Nur Imaziah Abu Bakar; Radhiatul Hasanah Abu Azmar @ Abu Azhar; Tan Sin Lee (2023)
E-waste has become a worldwide issue that is increasing every day. It includes valuable materials that can be disposed of for profit. Small appliances, large appliances, temperature exchange equipment, displays and monitors, IT or telecommunications devices, and lamps are part of the types of e-waste. Several studies have been conducted on the households. This study aims to examine the desire to dispose of e-waste among residents in Taman Bahau, Negeri Sembilan. This is a quantitative design where questionnaires have been used as a tool for data collection. Through a convenience sampling technique, 137 respondents involved in the survey. Descriptive analysis was used to describe the demographic background of the respondents, whilst Pearson Correlation has been employed to analyze the relationship of the variables using The Statistical Package for Social Science (SPSS) software latest version. The findings indicate that, attitudes, subjective norms and perceived behavioral control have a positive relationship with the desire to dispose of e-waste properly. As of the practical relevance, this research can help the community and other related parties to become more aware on saving the environment from destruction caused by improperly disposed electronic waste.